‘Fragile States’ in an Unequal World - Rocha de Siqueira, Isabel (Open Book Publishers, 2022)
This is a book about people. ‘Fragile States’ in an Unequal World: The Role of the g7+ in International Diplomacy and Development Cooperation introduces the members of the g7+, a group formed by 20 conflict-affected states: why they came to believe in politics and policy; how they feel about their work, their family and their communities; and what they want to leave behind for the next generations. It is the story of their personal and collective values, their mistakes, and the challenges they faced, and it will resonate with anyone who has tried to organize and work with a group of very different people.